Katie up and down the hall : the true story of how one dog turned five neighbors into a family - Plaskin, Glenn (New York : Center Street, 2010)
"The heartwarming true story of how one special cocker spaniel turned four strangers into family"--Provided by publisher.
Faux-paws -- Test-run dog -- The runt of the litter -- From bow to wow -- "Lion" in a cage -- News hound -- Prancing with the stars -- Walter the horse--favorites & foibles -- A real pearl -- Everything that goes up -- Canine cop -- Gentlemen prefer blondes -- "Ready, set, go!" -- The accident -- Party girls -- The talking picture frame -- Lady sings the blues -- The day our world stopped -- The escape -- Ghost town -- Granny in the ER -- Georgia peach -- Nocturne -- "Have a great time--and call me!" -- Love remains.
Keywords: Plaskin, Glenn; Cocker spaniels -- New York (State) -- New York -- Biography; Human-animal relationships -- New York (State) -- New York; Neighbors -- New York (State) -- New York -- Biography; Strangers -- New York (State) -- New York -- Biography; Families -- New York (State) -- New York; Battery Park City (New York, N.Y.) -- Biography; New York (N.Y.) -- Biography; Battery Park City (New York, N.Y.) -- Social life and customs; New York (N.Y.) -- Social life and customs